PRINSIP GOOD GOVERNANCE DALAM PENYELENGGARAAN PEMERINTAHAN DI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH PROVINSI SULAWESI TENGAH - Setiatama, Adifian Saputra; Mangngasing, Nasir; Natsir, Nawawi (Katalogis, 2019)
The purpose of this study was to determine the implementation of the principles of good governance in the administration of governance in the Central Sulawesi Regional Financial and Asset Management Agency. The theory used is the principle of good governance proposed by Edralin and Whitaker (2007: 35) where there are nine indicators to measure the level of implementation of good governance in government, namely public participation, rule of law, transparency, caring for stakeholders, consensus oriented, fair, effectiveness and efficiency, accountability and strategic vision. This type of research is a Qualitative Descriptive which attempts to tell and interpret data that is pleasing to the facts, using a purposive method, data collection and discussion with a qualitative analysis approach to collecting data and materials through observation and interviews with a total of five informants. Based on the results of the study it was found that the implementation of the principles of good governance in the administration of government in the Central Sulawesi Regional Financial and Asset Management Agency in the indicators of the rule of law, consensus oriented, fair, effectiveness and efficiency, accountability, strategic vision had been running optimally. However, for indicators of transparency, concern for stakeholders, public participation has not been running optimally due to the lack of supporting facilities in order to create easy access for the public to be able to obtain various information needed from the office including budget management through certain media such as media online that is easy for the public to access either anywhere and anytime.